Postcolonial Spatiality in Fiction : The case of Nuruddin Farah’s Maps - Lemlouma, Aicha; Selt, Djihad Afaf (My University, 2022)
By the late of the twentieth century, a ‘spatial turn’ has characterized all humanities and social sciences. Postcolonialism has directed a huge attention to colonial spatial practices since colonialism is primarily a struggle over geography. In this light, this project represents a closer examination of the representation of postcolonial spatiality in fiction, namely in Nuruddin Farah’s novel Maps (1986). The present study is conducted through the implementation of the geocritical approach to aid in understanding of how literary representation and spatiality interconnect, since geocriticism is the intersection of literature and geography. The analytical and descriptive methods are also applied to investigate the way characters produce different spaces. This aspect of space is studied in the light of Lefebvre’s theory of “production of space” as well as Soja and Bhabha’s concepts of “third space”. This study unveils the impact of the colonizer’s policies that pertain to the partition of Africa, notably; Somalia, on individuals and their process of space production. It ultimately finds out that the colonial inscription of boundaries and postcolonial national discourses have resulted in spatially torn individuals and an identity dilemma. Furthermore, these colonial cartographic policies along with postcolonial practices affect the characters’ own production of space, since they fail to create an alternative space where they can express their true identities and harmonically coexist. Essentially, this study recommends that the adherence to the colonial boundaries, that is mainly characterized by being exclusive, would more or less cause a rift within the African societies. Thus, alternative spaces where diversity is celebrated are highly recommended.